Dakwah Islam Masa Daulah Abbasiyah - Nashir, Muhammad (Jurnal Komunikasi Islam, 2012)
Abstract: This article discusses some aspects of Islamic proselytizing during the Abbasid Daula, especially from the geographical aspect of proselytizing, key figures, patterns of change, the content, its characteristics, and contextualization models that time compared to the contemporary reality, especially in Indonesia. This paper argues that the empire already developed Islamic proselytizing comprehensively in various fields of life. The valuable lesson from the history of proselytizing for today is the importance of the synergy between the authorities and the people in educating the preachers and carrying out the preaching programs.Keywords: aspects of Islamic proselytizing, Abbasid Daula, contemporary reality -----------------------------------------------------------------------Abstrak: Artikel ini membahas tentang aspek-aspek dakwah Islam pada masa Daulah Abbasiyah, baik dari aspek geografis dakwah, para tokoh kunci, bentuk perubahan dan konten dakwah, karakteristiknya serta kontekstualisasi model dakwah pada masa itu dengan realitas kontemporer, khususnya di negara Indonesia. Tulisan ini berargumentasi bahwa imperium ini telah mengembangkan dakwah Islam dengan sangat piawai dan komprehensif di berbagai bidang kehidupan. Sebuah pelajaran yang berharga dari sejarah dakwah untuk masa ini adalah pentingnya sinergi antara penguasa dan rakyat dalam mencetak da’i dan menjalankan program dakwah.Kata kunci: aspek dakwah Islam, daulah Abbasiyah, realitas komtemporer